Green Hydrogen Blending into the Tunisian Natural Gas Distributing System - Hadhami Bdioui; Hazem Touati; Maher Ben Chiekh; Angeles López-Agüera (Hydrogen)
It is likely that blending hydrogen into natural gas grids could contribute to economy-wide decarbonization while retaining some of the benefits that natural gas networks offer energy systems. Hydrogen injection into existing natural gas infrastructure is recognised as a key solution for energy storage during periods of low electricity demand or high variable renewable energy penetration. In this scenario, natural gas networks provide an energy vector parallel to the electricity grid, offering additional energy transmission capacity and inherent storage capabilities. By incorporating green hydrogen into the NG network, it becomes feasible to (i) address the current energy crisis, (ii) reduce the carbon intensity of the gas grid, and (iii) promote sector coupling through the utilisation of various renewable energy sources. This study gives an overview of various interchangeability indicators and investigates the permissible ratios for hydrogen blending with two types of natural gas distributed in Tunisia (ANG and MNG). Additionally, it examines the impact of hydrogen injection on energy content variation and various combustion parameters. It is confirmed by the data that ANG and MNG can withstand a maximum hydrogen blend of up to 20%. The article’s conclusion emphasises the significance of evaluating infrastructure and safety standards related to Tunisia’s natural gas network and suggests more experimental testing of the findings. This research marks a critical step towards unlocking the potential of green hydrogen in Tunisia.